Dendritic transport element of human arc mRNA confers RNA degradation activity in a translation‐dependent manner. (23rd September 2016) - Ninomiya, Kensuke; Ohno, Mutsuhito; Kataoka, Naoyuki
Abstract : Localization of mRNA in neuronal cells is a critical process for spatiotemporal regulation of gene expression. Cytoplasmic localization of mRNA is often conferred by transport elements in 3′ untranslated region (UTR). Activity‐regulated cytoskeleton‐associated protein (arc) mRNA is one of the localizing mRNAs in neuronal cells, and its localization is mediated by dendritic targeting element (DTE). As arc mRNA has introns in its 3′ UTR, it was thought that arc mRNA is a natural target of nonsense‐mediated mRNA decay (NMD). Here, we show that DTE in human arc 3′ UTR has destabilizing activity of RNA independent of NMD pathway. DTE alone was able to cause instability of the reporter mRNA and this degradation was dependent on translation. Our results indicate that DTE has dual activity in mRNA transport and degradation, which suggests the novel spatiotemporal regulation mechanism of activity‐dependent degradation of the mRNA. Abstract : The human arc DTE in 3′ UTR has mRNA‐destabilizing activity independent of nonsense‐mediated mRNA decay (NMD). Destabilizing activity of the arc DTE is dependent on translation.